Drought stress revealed physiological, biochemical and gene-expressional variations in 'Yoshihime' peach (Prunus Persica L) cultivar. Issue 1 (1st January 2018) - Haider, Muhammad S.; Kurjogi, Mahantesh M.; Khalil-ur-Rehman, Muhammad; Pervez, Tariq; Songtao, Jiu; Fiaz, Muhammad; Jogaiah, Sudisha; Wang, Chen; Fang, Jinggui
ABSTRACT: It is indispensable to comprehend the mechanism that regulates plant responses to drought conditions to intensify the water use efficiency of stone fruits. The physiological, biochemical and molecular responses of drought-treated peach leaves were investigated. Results revealed that drought-treated plants manifested a significant attenuation in water potential as compared to control plants. Furthermore, sorbitol and proline contents were accumulated contrary to glucose, fructose, and sucrose that were dwindled significantly throughout the drought period. Similarly, the activities of antioxidant enzymes and expression pattern of related genes were hoisted to counter the lipid peroxidation in drought-treated plants. Moreover, reduced stomatal conductance has repressed the photosynthesis process and linked genes during drought stress. The expression level of regulatory genes ( dehydration-responsive element-bindings and WRKYs ) exhibited up-regulation in the drought-treated group. Overall, this study asserts that 'Yoshihime' peach cultivar possesses unique physiological, biochemical, and molecular responses under different spells of drought stress.